“THE ROLE OF CRITICAL THINKING IN TEACHING ENGLISH" - Boboqulova Gulshoda Xusanovna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
ANNOTATION These days learning foreign languages are the essential demand of our society and English has become a universal language. The English language becomes the means of international communication, the language of trade, education, politics and economics. In today’s modernized society, all come across to the role of critical thinking while they are learning English. With the help of critical thinking, students can improve their knowledge stock deeply and use English in every field of life.